Postnatal Catch-Up Growth After Suspected Fetal Growth Restriction at Term - van Wyk, Linda; Boers, Kim E.; van Wassenaer-Leemhuis, Aleid G.; van der Post, Joris A. M.; Bremer, Henk A.; Delemarre, Friso M. C.; Gordijn, Sanne J.; Bloemenkamp, Kitty W. M.; Roumen, Frans J. M. E.; Porath, Martina; van Lith, Jan M. M.; Mol, Ben W. J.; et al. (Frontiers in Endocrinology, 2019)
Objective: To study growth patterns of children born after suspected fetal growth restriction (FGR) at term and to compare the effect of induction of labor (IoL) and expectant management (EM), also in relation to neurodevelopmental and behavioural outcome at age 2. Methods: We performed a 2 years’ follow-up of growth of children included in the DIGITAT study, a RCT comparing (IoL) with (EM) in pregnancies with suspected FGR at term. We collected data on child growth until the age of two years. Standard deviation scores (SDS) for height and weight were calculated at different ages. We assessed the effects of IoL compared with EM and the effects of a birth weight below or above the 3rd or 10th centile on catch-up growth. Target height SDS’s were calculated using the height of both parents. Results: We found a significant increase in SDS in the first two years. Children born after EM showed more catch-up growth in the first month (height: mean difference - 0.7 [95% CI: 0.2;1.3]) and weight (mean difference -0.5 [95% CI: 0.3; 0.7]) . Children born with a birth weight below the 3rd and 10th centile showed more catch-up growth after one (mean difference -0.8 SDS [95% CI: -1.1; -0.5]) and after two years (mean difference -0.7 SDS [95% CI: -1.2; -0.2]) as compared to children with a birth weight above the 3rd and 10th centile. SDS at birth had the strongest effect on adverse neurodevelopmental outcome two years of age. Conclusion: After FGR at term, postnatal catch-up growth is generally present and associated with the degree of FGR. Obstetric management in FGR influences postnatal growth. Longer-term follow up is therefore needed and should be directed at growth and physical health